Batch Adsorption of Whey Protein onto Anion Exchange Mixed Matrix Membrane Chromatography - S.M, Saufi; Conan, J.Fee (2010)
Mixed matrix membrane (MMM) chromatography is an advanced method for whey protein fractionation. The adsorption capacity of MP500 anion exchange MMM chromatography was evaluated by batch experiments using simulated whey containing a single whey protein component and real whey at pH 6. The binding preference for whey proteins was demonstrated to follow the order: β-lactoglobulin > bovine serum albumin > α-lactalbumin. MP500 based MMM could be used to recover β-lactoglobulin very selectively from whey to produce a single protein component for food ingredient and related applications.